Taking stock of the waqf-based Islamic microfinance model. Issue 8 (7th August 2017) - Abdullah, Rose; Ismail, Abdul Ghafar
Abstract : Purpose: The purpose of this paper is to explore two main aspects of waqf: the characteristics of waqf property and the management of waqf. This paper also discusses the governance of waqf management as a source of funds for Islamic microfinance institutions (MFIs). Design/methodology/approach: This research uses content analysis method to examine various literatures that discuss the concept and management of waqf. Findings: The characteristics of cash waqf such as permanence, irrevocability and perpetuity differentiate waqf from other type of donations. Therefore, cash waqf-based Islamic microfinance needs to be sustainable. Good corporate governance is vital to ensure the sustainability. As the donors of cash waqf do not aim to make financial profit, waqf-based Islamic MFIs will be able to provide low-cost capital to the poor entrepreneurs. Furthermore, to ensure the perpetuity of the waqf, it is suggested that only revenue from the waqf property should be used for microfinance fund. Social implications: The cash waqf-based Islamic microfinance will help the micro entrepreneurs to get low-cost capital without collateral. At the same time, public can donate any amount they afford to contribute to cash waqf. Originality/value: The creation of a cash waqf-based Islamic MFI must observe the issues of agency conflicts and the right of stakeholders to a transparent management. This paper emphasizes the importance of good governance in managing the waqf property as a source of fund for Islamic MFIs.